Faktor-Faktor Keterlambatan Surat Perintah Perjalanan Dinas Biro Umum dan Rumga Setda Provinsi Jawa Timur - Aliefia, Vony; Reviandani, Oktarizka (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Official trips by authorized officials to attend invitations, meetings, seminars, and others, especially in the government, require a Travel Duty Letter (SPPD) as proof of accountability. However, the processing of SPPD is not always smooth and on time due to various obstacles resulting in delays in the disbursement of travel funds. To identify the factors causing delays in SPPD, researchers used 4 main focuses: (1) Human Resource Factors, (2) Internal Control, (3) Technology and Information Factors, and (4) Dominant Factors. The research method used is qualitative descriptive with data collection techniques through in-depth interviews, observations, and documentation. The research results show that: (1) Human Resource Factors, have worked quickly in accordance with existing provisions, (2) Internal Control, internal factors still cannot be controlled because the mobility of the relevant leaders has a tight schedule, resulting in a backlog of files and stagnation in the submission process. External factors can still be followed up by the relevant implementers for timely delivery of invoices, as invoices are the main administrative requirement in SPPD, (3) Technology and Information Factors, still use manual methods in their work, using Microsoft Excel, so many tasks are not automatic and synchronized between one file and another, (4) Dominant Factors, delays are dominated by the busy mobility of leaders and late submission of supporting documents. These problems become factors in the delay of SPPD.